2018
DOI: 10.15575/psy.v5i2.3068
|View full text |Cite
|
Sign up to set email alerts
|

Keputusan Pemilihan Karir: Studi Komparatif pada Siswa Remaja Jurusan IPA dan IPS

Abstract: The purpose of this study was to compare career choice decisions between students majoring in Science and Social Sciences. This study used the comparative quantitative method. The subjects were 188 students, consists of 94 students on each major in Science and Social Science. The subjects were selected by purposive sampling, with the characteristics of class XII students majoring in science and social studies and aged 15-18 years. The data were analyzed using Mann-Whitney Nonparametric Test. The findings showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…((Kualitas Pendidikan Rendah, 2018. ) The results of preliminary research conducted by (Nuraqmarina & Risnawati, 2018) showed the condition of students of class XII MAN B Jakarta who entered the IPS department because of their insufficient grades to enter the IPA department. This causes anxiety and conflict in the student because the major he is currently working in is not in line with the major he wants.…”
Section: Introductionmentioning
confidence: 99%
“…((Kualitas Pendidikan Rendah, 2018. ) The results of preliminary research conducted by (Nuraqmarina & Risnawati, 2018) showed the condition of students of class XII MAN B Jakarta who entered the IPS department because of their insufficient grades to enter the IPA department. This causes anxiety and conflict in the student because the major he is currently working in is not in line with the major he wants.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the result of the research, using scrabble wall media in learning English, especially vocabulary will improve students' vocabulary mastery and implement students-centered learning in the class. The teaching and learning process would be an enjoyable and motivate students to achieve well (Nuraqmarina & Risnawati, 2018). Furthermore, the media used in the teaching and learning process can be a modification for popular media, so it would be the new media like what this study conducted.…”
Section: Discussionmentioning
confidence: 97%
“…Menentukan pilihan jurusan yang dapat menentukan karir di masa depan atau yang bidang ilmunya sesuai passion dan minat menjadi sesuatu yang cukup membingungkan bagi siswa SMK. Kebimbangan siswa kelas XII untuk masuk perguruan tinggi diantaranya adalah ragu dengan pilihannya (Nuqmarina & Risnawati, 2018). Banyaknya pilihan jenjang pendidikan, jenis pekerjaan, dan informasi yang beredar di masyarakat, menjadi faktor yang membuat siswa mengalami kebingungan dalam mengambil keputusan dan salah dalam memilih jurusan.…”
Section: Pendahuluanunclassified